Features of diagnostics of the hepatobiliary system diffuse lesions in children with herpes viral infection caused by Epstein-Barr virus (both isolated and in the form of mixed herpesvirus infection) - O. H. Hyliuk; L. M. Bulat (Zaporožskij Medicinskij Žurnal)
Purpose: to improve the treatment quality and prognosis of herpesvirus infection in children caused by the Epstein-Barr virus (both isolated and in the form of mixed herpesvirus infection) based on the study of clinical, biochemical and immunological parameters of the hepatobiliary system.